Working With Probate Inventories: A Class Assignment In Historical Methods - Hynes, Darren (Teaching History: A Journal of Methods, 2010)
Probate inventories are listings of property that were sometimes taken upon an individual's death. A team of appraisers would tour the home and lands of the deceased, describing everything of value and assigning an estimated worth. This appraisal would help the administrator or executor of the estate pay off all creditors, with the remainder being distributed according to a will or divided among heirs for those who died intestate. For the past four decades family historians as well as economic and social historians have made extensive use of these inventories, but it is hard to make generalizations about them, as laws governing them vary according to the jurisdiction and year being examined; the literature on probate inventories is consequently very wide-ranging. Used initially for the study of wealth distribution, researchers have also used them to investigate other areas of historical interest. For example, doctors' kits and libraries inform us about the material culture of medicine; word usage and spelling in the lists interest linguists as well as intellectual historians, who also find an indication of the degree of literacy in the number of documents signed by "x" rather than a name; in named books and ownership of Bibles there is evidence of learning and intellectual interests; pottery, dishware, and utensils interest archaeologists; sociologists find status symbols in the details of furnishings, apparel, and cultural objects; agricultural implements tell of farming methods and crop specialization; horses, harness, wagons, and boats indicate modes of production as well as travel; tools speak of craftsmanship; household implements like spinning wheels, wool cards, looms, and soap kettles suggest household production. We can also examine patterns such as the seasonal round of work and the sexual division of labor.